PENGARUH BERBAGAI DOSIS PUPUK ORGANIK CAIR LIMBAH RUMAH TANGGA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI GOGO - Izni Izni; Aris Aksarah Pas; Jumardin Jumardin (Jurnal Agrotech, 2019)
This study aims to study the growth response and yield of gogo rice at various doses of household waste organic fertilizer. This study uses a randomized block design (RAK) of one factor. Grouping based on sunlight. The treatment that was tried was various doses of household organic liquid fertilizer (POC), namely, POC0 = without POC, POC1 = 200 ml / plant, POC2 = 250 ml / plant, POC3 = 300 ml / plant. The results showed that the treatment of various doses of liquid organic fertilizer had a significant effect on the growth and yield of gogodan rice and the treatment dose of 300 ml / plant had a higher effect compared to other treatments on the growth and yield of gogo rice plants.